2019
DOI: 10.1057/s41599-019-0217-x
|View full text |Cite
|
Sign up to set email alerts
|

Framing effects on public support for carbon capture and storage

Abstract: Carbon Capture and Storage (CCS) involves trapping carbon dioxide (CO 2) from power generation and heavy industrial processes and directing it into long-term geological storage (e.g., in depleted oil fields or saline aquifers). In doing so, CCS could facilitate global carbon abatement efforts. Yet, it remains controversial with high-profile public opposition to particular CCS developments. For instrumental, normative and substantive reasons, it is increasingly recognised that public acceptance of CCS as a vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
101
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(108 citation statements)
references
References 33 publications
7
101
0
Order By: Relevance
“…Karimi et al [36] found that although cultural characteristics did influence public perceptions of CCS and its potential risks, responses were unlikely to be predicted by cultural factors alone, highlighting the critical role of contingent factors at a local scale. Whitmarsh et al [10] found marked differences in awareness of and support for CCS between the countries included in the study (Netherlands, Canada, Norway, USA, UK). The greatest support was reported in the UK where, for example, storage sites will be located offshore and the lowest in the Netherlands, which has previously seen high-profile opposition to a proposed project [37].…”
Section: Geographical Contexts and Place-based Studiesmentioning
confidence: 90%
See 4 more Smart Citations
“…Karimi et al [36] found that although cultural characteristics did influence public perceptions of CCS and its potential risks, responses were unlikely to be predicted by cultural factors alone, highlighting the critical role of contingent factors at a local scale. Whitmarsh et al [10] found marked differences in awareness of and support for CCS between the countries included in the study (Netherlands, Canada, Norway, USA, UK). The greatest support was reported in the UK where, for example, storage sites will be located offshore and the lowest in the Netherlands, which has previously seen high-profile opposition to a proposed project [37].…”
Section: Geographical Contexts and Place-based Studiesmentioning
confidence: 90%
“…One of the earliest studies, which does distinguish between different sources of CO 2 , [9], found that fossil fuel sources of CO 2 were perceived less favourably by survey respondents than industrial or bioenergy sources. Whilst research has started to consider different applications for carbon capture (e.g., carbon capture and utilisation (CCU) [10]), we found that BECCS is often compared with other CDR technologies (e.g., [11]), or other sources of CO 2, (e.g., [12,13]) rather than considered on its own. More favourable responses to CCS have been observed when it is combined with bioenergy and increased support has been reported for CCU-notably amongst climate sceptics, for whom addressing concerns about waste carried greater traction than climate change mitigation [10].…”
Section: Beccs Is Part Of the Ccs Familymentioning
confidence: 99%
See 3 more Smart Citations